2019
DOI: 10.36303/sajaa.2019.25.4.2191
|View full text |Cite
|
Sign up to set email alerts
|

SASS: South African Simulation Survey – a review of simulation-based education

Abstract: Background: Simulation-based education (SBE) has been shown to be an effective and reproducible learning tool. SBE is used widely internationally. The current state of SBE in South Africa is unknown. To the best of our knowledge this is the first survey that describes the use and attitudes towards SBE within South Africa. Methods: An online survey tool was distributed by email to: i) the South African Society of Anaesthesiologists (SASA) members; and ii) known simulation education providers in South Africa. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The Healthcare Simulation Dictionary provides two descriptions of a facilitator, namely, an individual participating in any part of simulation implementation and/or delivery, or an individual directly facilitating the achievement of a desired outcome in an SBLE [ 32 ]. Due to the various roles fulfilled by educators in the simulated environment [ 33 , 34 ], careful consideration was given to labelling the element of competent facilitator. Opting for the term, facilitator, implies that the educator is not necessarily required to participate in all framework phases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Healthcare Simulation Dictionary provides two descriptions of a facilitator, namely, an individual participating in any part of simulation implementation and/or delivery, or an individual directly facilitating the achievement of a desired outcome in an SBLE [ 32 ]. Due to the various roles fulfilled by educators in the simulated environment [ 33 , 34 ], careful consideration was given to labelling the element of competent facilitator. Opting for the term, facilitator, implies that the educator is not necessarily required to participate in all framework phases.…”
Section: Discussionmentioning
confidence: 99%
“…Opting for the term, facilitator, implies that the educator is not necessarily required to participate in all framework phases. Notably in educational environments where there is a shortage of healthcare educators [ 6 ], especially educators trained in the use of simulation as educational methodology [ 33 ], and limited institutional financial resources [ 6 , 28 ], makes identification of facilitative roles when integrating the framework essential. The authors suggest that appropriate educators be identified for the various facilitative roles required by the framework.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maintaining a safe learning environment could explain why stability was only achieved in the Delphi survey on statements relating to the student-to-educator ratio during formative and summative assessments, as SBLEs are not routinely used during either immersive or practical skills-based assessments in SA healthcare education. [27] The use of SBLEs for summative assessments therefore requires further investigation. If, however, SBLEs were to be considered for use, especially in summative assessments, identification of valid and reliable assessment tools during the planning phase is essential, [25] which was confirmed by the panel members.…”
Section: Researchmentioning
confidence: 99%
“…[4] Research has been published on the application of high-technology clinical simulation as a training tool for specific clinical scenarios in South Africa (SA). [7][8][9][10] However, little has been reported on the operational approach taken and challenges faced when creating and running a high-technology clinical simulation facility in SA. Swart et al [7] stated that financial constraints to obtain simulators and a lack of dedicated simulation technicians, trained educators and time for simulation activities are the major barriers to simulation implementation.…”
mentioning
confidence: 99%